KOMUNIKASI INTERPERSONAL DALAM PELAYANAN PSIKOSOSIAL TRAUMA HELAING PADA ANAK KORBAN KEKERASAN SEKSUAL DI P2TP2A KOTA TANGERANG - Asriyani Sagiyanto (Universitas Bina Sarana Informatika, 2020)
Woman victims of violence contrives problems on stability of psychological function which needs a quick and effective treatment in favor of being healed from trauma. This study aims to determine the communication patterns applied by the psychosocial service officers integrated service centers for empowering women and children (P2TP2A) Tangerang city and the stages of their handling. The research is a qualitative descriptive study with data collection using the method of observation, interviews, and documentation. The results showed that the communication patterns used by psychosocial service workers to victims of sexual violence in assisting trauma are fun communication patterns using lots of playing methods (colour cues, role playing). The method of handling victims is carried out with trauma healing stages carried out in the form of: Psychological First Aid, Cognitive Behavioral Therapy, Talk Therapy. The stage is given to adjust the attainment of the victim’s conditions. The stages are repeated for a minimum of 4 meetings and a maximum of 6 meetings adjusting to the victim’s achievement. Providing treatment to children is classified by age.